SISTEM PENAMAAN ORANG BALI - Temaja, I Gede Bagus Wisnu Bayu (Faculty of Humanities, Diponegoro University, 2017)
This research belonged to the field of anthropological linguistics. This research aimed atexplaining the naming system of Balinese people.Based on several previous studies, this research focused on the system of Balinese people’s name in general.It was an anthropological linguistic research concerned on the relation between lingual aspects in the form of naming system and its cultural relations of the Balinese society. The research methodology was conducted into three steps, consist of: 1) data collection which was conducted by implementing interview method through recording and taking a note techniques, as well as literature-based research method; 2) data analysis which was conducted by implementing qualitative approach of interactive model; 3) data display which was conducted by explaining the data informally and displaying it on the table. The results show that there are three aspects that influence naming system of Balinese people, such as 1) sex, 2) birth order, and 3) caste system. Those aspects provided framework related to reference of Balinese name. This results reflect that the lingual aspect of naming system is influenced by cultural aspects, and therefore it represents the Balinese culture itself